Heat Transfer Processes in Oscillatory Flow Conditions - Artur J. Jaworski (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Heat exchange processes in steady flows have been studied extensively over the last two hundred years, and are now a part of undergraduate syllabi in most engineering courses. However, heat transfer processes in oscillatory flow conditions are still not very well understood. Their importance is well recognized in applications including Stirling machines, thermoacoustic engines, and refrigerators or pulsed-tube coolers in cryogenics. Additionally, the enhancement of heat transfer by using oscillatory, and, in some cases, pulsating flows is important in many areas of mechanical and chemical engineering for the intensification of heat transfer processes and possible miniaturization of heat exchangers of the future. This Special Issue was intended as a dissemination platform for researchers working in the field to have an opportunity to consolidate recent advances in this important research area. All types of research approaches were invited, including experimental, theoretical, computational fluid dynamics (CFD), and their combinations, while the approaches could be either of a fundamental or applied nature. The guest editor and the editorial team of Applied Sciences hope that the readership will find the selection of ten articles presented here a useful contribution to the emerging field of heat transfer processes in oscillatory flow conditions.